Effect of Price, Brand Image, and Trust on Consumer Satisfaction at Yamaha Mio in Arista Tajur - Yulianingsih; Rachmat Gunawan; Fitriani (International Journal of Managemen Analytics (IJMA), 2023)
This study aims to analyze and identify the effect of price, brand image, and trust both simultaneously and partially on customer satisfaction at Yamaha Mio at Arista Tajur. Questionnaires were distributed to 100 respondents who were taken by purposive sampling technique with criteria; consumers who have purchased Yamaha Mio motorbikes and consumers who are seen as mature enough to fill out the questionnaire, at least seventeen years old, the reason that they have been able to determine the satisfaction received rationally. The questionnaire was tested with validity tests, reliability tests, and also classic assumption tests. The results of these tests are valid, reliable, and can be used for regression data. The analytical method used in this study is a descriptive and verification method with a quantitative approach. The results of the study show that the variables of price, brand image, and trust simultaneously or partially have a positive and significant effect on customer satisfaction at Yamaha Mio at Arista Tajur. The test results for the coefficient of determination (R Square) are 57.6% while the remaining is 42.4%. The relationship between price, brand image, and trust is very strong with a correlation coefficient of 0.759